Fine needle aspiration cytology in the diagnosis of Tuberculous lymphadenitis and utility of Ziehl Neelsen stain benefits and pitfalls - Shruti Vimal; Arpana Dharwadkar; Shrish S Chandanwale; Vandana Verma; Anushree Khandelwal (International Journal of Medical Research and Review, 2016)
Introduction: In a developing country like India, tuberculous lymphadenitis is one of the most common presentations at OPDs. However, anti-tubercular treatment cannot be administered only on clinical suspicion. Cytomorphology with acid fast staining proves to be a valuable tool in diagnosing these cases along with culture. The study was undertaken to study the utility, limitations of fine needle aspiration cytology and various cytomorphological presentations in reference to Ziehl-Neelsen staining in tuberculous lymphadenitis and correlate the culture findings.Methods: The study was conducted for duration of two years with total of 170 cases at a tertiary care centre. The patients with clinically suspected lymphadenopathy were selected.Results: The incidence of tuberculous lymphadenitis was 68.8%. Overall AFB positivity was 64.1 %. Epithelioid cell granulomas with lymphocytes were the most common cytological picture and cases showing necrosis had highest AFB positivity. Maximum patients presented in second to fourth decade of life. Cervical region was the most common site of involvement with solitary lymphadenopathy as the most common presentation in contrast to matted lymph nodes as reported by others.Conclusion: Yet again Fine needle aspiration cytology is a safe, cheap and reliable procedure requiring minimal instrumentation and is highly sensitive to diagnose tuberculous lymphadenitis. The diagnostic index can be further increased by complementing cytomorphology with acid fast staining and culture techniques. However FNAC complimented with techniques like ELISA and PCR would give better dimensions to the current scenario of diagnosis and treatment modalities.